MEDIATING FINANCIAL AND HSE ROLES IN RISK MANAGEMENT IMPACT ON MYANMAR CONSTRUCTION SUCCESS - Aung, Theingi; Liana, Sui Reng; Htet, Arkar; Bhaumik, Amiya; Poddar, Sandeep (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This study seeks to examine the effects of risk management strategies on the success of construction projects in Myanmar, a country with a rapidly expanding construction industry that has received little scholarly attention. Using a combination of traditional paper-based surveys and online questionnaires, a comprehensive dataset has been compiled for this study. The participants, which included project managers, project engineers, safety engineers, financial experts, and project proprietors, played a crucial role in providing diverse perspectives. From the initial sample of 500 questionnaires, a response rate of 84.6 percent yielded 397 valid responses. Using Smart PLS as a data analysis instrument, the study deconstructed risk management into its fundamental components: identification, analysis, response, and monitoring. In addition to the immediate effects, the study reveals the intermediate roles played by financial performance and Health, Safety, and Environment (HSE) issues. The findings indicate a correlation between the implementation of effective risk management strategies and the overall success of construction projects. The intermediate effect of financial performance and HSE performance strengthens the relationship between these variables. This research offers significant academic and practical insights by providing evidence-based strategies to improve risk management practices in Myanmar's rapidly developing construction industry.